PENERAPAN LAPORAN KEUANGAN ORGANISASI NIRLABA BERDASARKAN PSAK NO. 45 - Andi Marlinah; Ali Ibrahim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This research to know the financial statement Mosque of Al-Markaz Al-Islami Jenderal M. Jusuf in accordance with SFAS 45 or not yet. The reseacrh method used descriptive qualitative that is direct by observation, interviews, and literatur study, with the stages of analysis data collection, data reduction, data triangulation, and conclusion. The research results obtained in Mosque of Al-Markaz Al-Islami Jenderal M. Jusuf is financial statement on Mosque of Al-Markaz Al-Islami Jenderal M. different with SFAS 45 which follows the format of the financial statement of Mosque of Al-Markaz Al-Islami Jenderal M. Jusuf.